Triple Combination Therapy With PD-1/PD-L1, BRAF, and MEK Inhibitor for Stage III–IV Melanoma: A Systematic Review and Meta-Analysis - Liu, Ye; Zhang, Xilan; Wang, Guoying; Cui, Xinchang (Frontiers in Oncology, 2021)
Triple combination of anti-PD-1/PD-L1 immunotherapy and anti-BRAF plus anti-MEK targeted therapy is a promising antitumor strategy and is increasingly being used in clinical trials. To evaluate the safety and efficacy of triple combination of PD-1/PD-L1, BRAF, and MEK inhibition in patients diagnosed with stage III-IV melanoma, we performed a systematic review and meta-analysis of randomized controlled trials (RCTs). The PubMed, EMBASE and Cochrane Library were searched for all studies published from inception to January 2021. The progression free survival (PFS), overall survival (OS), overall response rate (ORR), and risk of adverse events (AEs) were extracted by two independent investigators and pooled hazard ratio (HR) or risk ratio (RR) with 95% CI were determined using the random-effect model for data synthesis. Overall, five randomized controlled trials encompassing 1266 patients with stage III-IV melanoma were selected. Triple combination therapy significantly improved PFS (HR = 0.71; 95% CI = 0.59 to 0.86; P = 0.0005) and 2-year OS (RR = 1.12; 95% CI = 1.03 to 1.23; P = 0.01), but had no impact on ORR (RR = 1.09; 95% CI = 0.91 to 1.30; P = 0.37) when compared with controlled treatment group. In addition, triple combination therapy was associated with increased risks of hypothyroidism, arthralgia, myalgia, ALT increased, AST increased, asthenia and pyrexia compared with control group. Triple combination therapy of PD-1/PD-L1, BRAF, and MEK inhibition achieved better survival benefits but had higher incidence of some adverse events over two-drug combination or monotherapy. Further randomized controlled clinical trials are needed to verify our results.